Pengaruh Brand Ambassador Dan Brand Awareness Terhadap Keputusan Pembelian Yang Dimoderasi Brand Image pada E-Commerce Shopee (Studi Kasus pada Mahasiswa Aktif FEB UNISMA Angkatan 2021) - Ashrory, Ahmad Nuril; Rachma, N; Primanto, Alfian Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this study is to investigate whether brand image can moderate the influence of brand ambassadors and brand awareness on purchasing decisions. The research method used is a quantitative approach. This study uses explanatory research and moderated regression analysis (MRA) methods to test the proposed research model. The sample of this study were 100 active students of FEB UNISMA class of 2021. The hypothesis was tested using instrument testing, normality test, classical assumption test, moderated regression analysis, hypothesis testing, and coefficient of determination using SPSS v25. The findings indicated that 1) Brand ambassadors have a significant and positive effect on consumer decisions to make purchases, 2) Brand awareness has a significant and positive effect on consumer decisions to make purchases, 3) Brand image reduces the impact of brand ambassador influence on purchasing decisions, 4) Brand image reduces the impact of brand awareness on purchasing decisions. Keywords: Brand Ambassador, Brand Awareness, Brand Image, Purchasing Decisions